Harmful Alcohol Use Among Healthcare Workers at the Beginning of the COVID-19 Pandemic in Kenya - Jaguga, Florence; Kwobah, Edith Kamaru; Mwangi, Ann; Patel, Kirtika; Mwogi, Thomas; Kiptoo, Robert; Atwoli, Lukoye (Frontiers in Psychiatry, 2022)
Background: Healthcare workers play a key role in responding to pandemics like the on-going COVID-19 one. Harmful alcohol use among them could result in inefficiencies in health service delivery. This is particularly concerning in sub-Saharan Africa where the health workforce is already constrained. The aim of this study is to document the burden and correlates of harmful alcohol use among healthcare workers at the beginning of the COVID-19 pandemic in Kenya with the aim of informing policy and practice. Methods: This study was a cross-sectional analysis of data obtained from a parent online survey that investigated the burden and factors associated with mental disorders among healthcare workers during the COVID-19 pandemic in Kenya. We analyzed data obtained from a sub-population of 887 participants who completed the Alcohol Use Disorder Identification Test questionnaire. We used descriptive statistics to summarize the socio-demographic characteristics of the participants and multivariate analysis to determine the factors associated with harmful alcohol use. Results: Three hundred and eighty nine (43.9%) participants reported harmful alcohol use. The factors significantly associated with increased odds of endorsing harmful alcohol use were: being male (AOR= 1.56; 95% CI=1.14, 2.14; p=0.006), being unmarried (AOR= 2.06; 95% CI=1.48, 2.89; p<0.001), having 11-20 years of experience as compared to having 20+ years of experience (AOR= 1.91; 95% CI=1.18, 3.12; p=0.009), and being a specialist (AOR=2.78; CI=1.64, 4.78; P=<0.001) or doctor (AOR= 2.82; 95% CI=1.74, 4.63; p<0.001) as compared to being a nurse. Conclusions: A high proportion of healthcare workers reported harmful alcohol use at the beginning of the COVID-19 pandemic in Kenya. Males, the unmarried, those with 11-20 years of experience in the health field, doctors and specialists, were more likely to report harmful alcohol use. These findings highlight the need to institute interventions for harmful alcohol use targeting these groups of healthcare workers in Kenya during the COVID-19 pandemic in order to optimize functioning of the available workforce.